Good vs. Fair and Clean: An Analysis of Slow Food Principles Toward Gastronomy Tourism in Northern Iran. Issue 1 (2nd January 2022) - Payandeh, Ebrahim; Allahyari, Mohammad S.; Fontefrancesco, Michele F.; Surujlale, Jhalukpreya
ABSTRACT: In the tourism sector, food is of great importance, and one of the main concerns of tourists for short- and long-term trips is the choice available. In particular, in the past few years, rising demand for local gastronomy has emerged, which is still to be fully understood. The purpose of this study was to investigate the factors affecting the desire for local food among tourists and travelers in the northern region of Guilan (Iran). The paper presents the results of quantitative research conducted among tourists and travelers. Data were collected through a questionnaire, whose reliability, as measured by Cronbach's alpha method, was higher than the acceptable value of 0.7. Motivations were clustered around the three categories of Good, Fair, and Clean, which are inspired by the motto of the slow food movement. The findings of this research shed light on the hierarchy of values of tourists, suggesting that the Good factor was the key issue motivating their choice, while Fair and Clean had secondary roles. This research suggests that motivation does not preclude the implementation of positive initiatives relating to sustainability, but rather raises questions about the right form of communication concerning local cuisine to be employed.